Plant metal interaction : emerging remediation rechniques - Ahmad, Parvaiz (Elsevier, 2016)
Plant Metal Interaction: Emerging Remediation Techniques covers different heavy metals and their effect on soils and plants, along with the remediation techniques currently available. As cultivable land is declining day-by-day as a result of increased metals in our soil and water, there is an urgent need to remediate these effects. This multi-contributed book is divided into four sections covering the whole of plant metal interactions, including heavy metals, approaches to alleviate heavy metal stress, microbial approaches to remove heavy metals, and phytoremediation.- Resumé vydavatel
Keywords: rostliny; těžké kovy; biogeochemie; fytoremediace; biotechnologie; plants; heavy metals; biogeochemistry; phytoremediation; biotechnology; elektronické knihy; sborníky; electronic books; papers of several authors